Bridging theory and practice: Mentorship from practicing teachers in microteaching for preservice English teachers - Nunik Sugesti; Amrih Bekti Utami; Ihtiara Fitrianingsih; Nuriska Noviantoro; Dwiyani Pratiwi (Universitas Islam Sultan Agung, 2026)
This study examines the role of practicing teachers in a microteaching course and its impact on developing student-teachers’ skills at an Indonesian public university. This study specifically aimed to 1) identify student experiences in microteaching sessions involving practicing teachers, 2) analyze the influence of this involvement on their teaching skills, and 3) explore the meaning of this collaboration from the students’ perspectives. Using a qualitative phenomenological approach, the research involved third-year student-teachers, four lecturers, and ten practicing teachers from secondary schools in Yogyakarta. Data were collected through interviews, classroom observations, and reflection notes, then analyzed using Interpretative Phenomenological Analysis with source triangulation and member checking for validation. First, regarding student experiences, practicing teachers’ presence created an authentic and reflective learning environment where student-teachers engaged in microteaching that closely simulated real classroom situations. Second, concerning the influence on teaching skills, this collaboration significantly enhanced student-teachers’ abilities to design realistic lesson plans, conduct interactive teaching, manage classrooms effectively, and provide reflective assessment through direct guidance, modeling, and professional feedback. Finally, from the students’ perspective, practitioners were viewed not merely as technical mentors but as mediators between theory and practice and as professional role models who helped shape their teaching identity and self-reflection. The study concludes that collaborative microteaching effectively bridges academic learning and practical pedagogy. Sustained implementation within teacher education curricula is recommended to strengthen university-school partnerships and prepare future-ready educators.